2002
DOI: 10.1016/s0260-6917(02)90756-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-registration nurse education in pharmacology: is it adequate for the roles that nurses are expected to fulfil?

Abstract: Nurse education has undergone many changes over the last 30 years in line with the changing expectations of the nurse's role. A review of the literature suggests that nurses are inadequately prepared for their role in medication administration. With the introduction of nurse prescribing, the issue of education in pharmacology is becoming increasingly important. This paper describes a study conducted via a questionnaire survey of all nurse education institutions in England. The aim of the survey was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Results from many studies indicate that nurses lack adequate pharmacological skills for practice (Latter et al. 2000, Manias & Bullock 2002, Morrison‐Griffiths et al. 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Results from many studies indicate that nurses lack adequate pharmacological skills for practice (Latter et al. 2000, Manias & Bullock 2002, Morrison‐Griffiths et al. 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The same cannot be said of nurses, however, who are experienced in clinical examination and patient consultation but whose training has moved away from the biological to the social model of care [12]. Indeed, pharmacology has been specifically identified as an area of weakness in nursing education, both in the U.K. and elsewhere [7,8,13,14]. The implications of this for NMP education and ultimately patient safety are profound [15].…”
Section: Introductionmentioning
confidence: 99%
“…With the shift in pre-registration nurse training away from a medical model to a social model of care the level of biological science knowledge and understanding gained by pre-registration nurses has significantly reduced [ 9 ]. Indeed a number of studies have identified pharmacology education as an area of significant weakness both in the UK and elsewhere [ 10 - 12 ]. The implications of this for nurse prescribing education are profound [ 13 ] with a number of studies suggesting that both nurse prescribing students and educators recognise the problems associated with providing an adequate level of pharmacology input into these courses.…”
Section: Introductionmentioning
confidence: 99%